Market opportunities seizing capability and fish farming firm performance: A dynamic managerial capability perspective - Albertine M. Houessou; Augustin K.N. Aoudji; Gauthier Biaou; Anne Floquet (Heliyon, 2023)
The role that owner-managers’ managerial capabilities play in agricultural firms' strategic change and performance is still unclear. A firm's market opportunities seizing capability (OSC) is a source of competitiveness and superior performance. The objective of this study is to establish how owner-manager's dynamic managerial capabilities (DMCs) including managerial human capital, managerial social capital and managerial cognition affect firm performance through the mediating effect of OSC, as well as the moderating effect of market dynamism in the relationship OSC and firm performance. 306 cross-sectional data collected at fish farming firms (FFF) level in southern Benin were used and partial least squares structural equation model was applied to test research hypotheses. The results of SmartPLS4 reveal that owner-managers’ DMCs including business ties (BTs), political ties (PTs), and managerial cognition (MC) demonstrate a significant effect at improving FFF market OSC and performance. Finding also underline the significant contribution of market dynamism to FFF performance as well the mediating role of market OSC in the relationship between BTs, PTs, MC, and FFF performance. Findings suggest that FFF owner-managers can achieve superior performance by strengthening their DMCs while improving market OSC. The study provides useful insights to FFF owner-managers, agriculture policymakers and practitioners who are engaged in agriculture firms' strategic management and sustainable performance.